Noisy talk - Andreas Blume; Oliver J. Board; Kohei Kawamura (Theoretical Economics, 2007)
We investigate strategic information transmission with communication error, or noise. Our main finding is that adding noise can improve welfare. With quadratic preferences and a uniform type distribution, welfare can be raised for almost every bias level by introducing a sufficiently small amount of noise. Furthermore, there exists a level of noise that makes it possible to achieve the best payoff that can be obtained by means of any communication device. As in the model without noise, equilibria are interval partitional; with noise, however, coding (the measure of the message space used by each interval of the equilibrium partition of the type space) becomes critically important.
Keywords: C72; D82; D83; 330; Communication; information transmission; cheap talk; noise